A new ECG sign of an accessory pathway in sinus rhythm: pseudo partial right bundle branch block. Issue 2 (1st August 1999) - Lau, E W; Ng, G A; Griffith, M J
Abstract : It is clinically important to be able to detect the presence of an accessory pathway, as pre-excited atrial fibrillation is a well recognised cause of sudden cardiac death, for which there is a potential "cure" in the form of radiofrequency ablation of the pathway. The classic manifestations such as a shortened PR interval or delta waves may not always be present. In certain patients a pseudo partial right bundle block pattern—that is, an rSr′ complex in lead V1— may be the sole manifestation of a left sided accessory pathway. An electrophysiological mechanism is proposed for this pattern and it is suggested that this pattern may be used as a new ECG sign for diagnosing an accessory pathway in sinus rhythm.